SIMULATION OF FAST MAGNETOACOUSTIC WAVES IN THE SOLAR CORONAL MAGNETIC STRUCTURES - B. B. Mikhalyaev; G. A. Mankaeva; L. N. Dzhimbeeva; O. V. Hongorova; S. B. Derteev (Современная наука и инновации, 2022)
MHD waves in force-free magnetic arcades describing bipolar solar active regions are studied. The geometric acoustics approximation is used in cases where the wavelength is small compared to the scale of the inhomogeneity. It allows simple mathematical models to study phenomena such as wave refraction or wave propagation in waveguides. The eikonal method allows us the analytical study of short waves which are divided into Alfven and magnetoacoustic waves. The eigen-modes of magnetic arcades are formed as a result of their reflection at the photosphere.